Ashwagandha (Withania somnifera) in Cancer Therapy: Anticancer Activities and Their Mechanisms - Piecuch, Dawid; Sobota, Weronika; Zwoliński, Michał; Piskorz, Przemysław; Hańczyk, Edyta; Zemsta, Katarzyna; Kulesza, Bartłomiej (Quality in Sport, 2024)
Cancers are characterized by rapid development of abnormal cells that multiply uncontrollably, leading to invasive tumors. By 2040, new cancer cases worldwide are expected to reach 30.2 million. In response, research focuses on the anti-cancer properties of ashwagandha (Withania somnifera), used in traditional Indian medicine. Ashwagandha exhibits anti-inflammatory effects by modulating pathways like NF-kB, Nrf2/HO-1, JAK-STAT, MAPK, and NLRP3, reducing cancer-related inflammation. It also has strong antioxidant properties due to compounds like withanolides, increasing antioxidant enzyme activity and reducing oxidative stress, potentially lowering cancer risk. Ashwagandha extract shows cytotoxic effects against cancer cells, inducing apoptosis and arresting cells in the resting phase, leading to DNA damage in cancer cells. It inhibits angiogenesis, the process of forming new blood vessels that supply tumors, through mechanisms such as VEGF inhibition and reduced macrophage infiltration. Additionally, ashwagandha modulates T lymphocytes and cytokine production, enhancing the immune response against cancer, and stimulates NK cell activity, crucial for controlling tumor growth and development. Supplementation with ashwagandha reduces cortisol levels and improves cognitive functions and quality of life in people experiencing stress, potentially lowering cancer risk. Research suggests ashwagandha may be a valuable addition to anti-cancer therapy, acting on various levels of cancer pathogenesis. However, further clinical studies are needed to fully understand its mechanisms of action and to evaluate its efficacy and safety in cancer treatment.